Global R-matrix analysis of the 11B(α, n)14N reaction. (October 2020) - deBoer, R. J.; Liu, Q.; Chen, Y.; Couder, M.; Görres, J.; Lamere, E.; Long, A.M.; Lyons, S.; Manukyan, K.; Morales, L.; Robertson, D.; Seymour, C.; et al.
Abstract: Reactions that populate the 15 N system have implications for nucleosynthesis through the 11 B( α, n ) 14 N and 14 N( n, p ) 14 C reactions and the 14 N( n, p ) 14 C reaction is also a key component in modeling atmospheric 14 C production. A convenient characteristic of this system is that the α -particle, proton, and neutron separation energies are all within ≍1 MeV of one another. Further, it has been observed that 11 B+ α, 14 N+ n and 14 C+ p induced reactions all populate many of the same resonances near their reaction thresholds. This strongly facilitates the simultaneous analysis of data for all three of these entrance partitions using a global R-matrix analysis, which in turn provides a method of comparing the consistency among the different experimental measurements. In this work, a new measurement has been performed for the 11 B( α, n ) 14 N reaction, which gives a more accurate description of the cross section, in particular over an important interference region. This new data is combined with results from previous measurements, which populate a similar excitation energy range in the 15 N system, to produce a global fit that includes 11 B( α, n ) 14 N reaction data for the first time.